FACTORS AFFECTING THE DECISION TO PURCHASE CLOTHING AT MATAHARI DEPARTMENT STORE, LIPPO PLAZA KENDARI BRANCH - Haerani, Cecen; Titop, H. Herman; ., Suharlian (Sultra Journal of Economic and Business, 2021)
This study aims to determine the factors that influence the decision to buy clothes at Matahari Department Store, Lippo Plaza Kendari Branch. The sample in this study were as many as 40 respondents who were taken by census who were consumers who had shopped at Matahari Department Store, Lippo Plaza Kendari Branch. This study uses multiple linear regression analysis toolsThe study found that simultaneously product quality, price and brand image had a positive and significant effect on consumer purchasing decisions. Partially found: 1) product quality has a positive and significant effect on consumer purchasing decisions; 2) price has a positive and significant effect on consumer purchasing decisions and 3) brand image has a positive and significant effect on consumer purchasing decisions.